Kajian Literatur Risiko Keselamatan dan Kesehatan Kerja serta Lingkungan (K3L) dalam Pembangunan Gedung di Indonesia - Desnalia, Desnalia; Waruwu, Petrus Candra Foera Era (CV. SINAR HOWUHOWU, 2024)
Occupational Safety, Health, and Environment (K3L) are crucial aspects of building construction in Indonesia. According to data from the Ministry of Manpower, the construction sector accounted for 30% of total workplace accidents in Indonesia in 2020. Additionally, economic losses due to workplace accidents in this sector reached IDR 1.2 trillion in 2019. This literature review aims to identify K3L risk factors in building construction in Indonesia and formulate effective mitigation strategies. The research method used is a qualitative descriptive method with content analysis techniques. The results of the review indicate that the lack of training and awareness among workers, unstable environmental conditions, and suboptimal government regulations and policies are the main factors affecting K3L risks. Increased training, the application of advanced technology, and strengthened regulations are needed to reduce K3L risks and create a safer and healthier work environment.